A numerical model of pin thread effect on material flow and heat generation in shear layer during friction stir welding. (December 2018) - Sun, Z.; Wu, C.S.
Highlights: Special equations are derived to describe the effect of pin thread on the material flow velocity inside thread grooves. The equations are combined with CFD model to analyze the effect of pin thread on heat generation and material flow in FSW. The enhancement of material flow near pin side for threaded pin is analyzed compared with that for unthreaded pin. The effect of pin thread on temperature profile and area of TMAZ are numerically simulated. The predicted thermal cycle and TMAZ geometry are in good agreement with the experimentally measured ones. Abstract: A novel method is proposed to analyze the effect of pin thread on the heat generation, temperature distribution and material flow field in friction stir welding (FSW). Based on the analysis of the interaction force between the thread groove and the workpiece material, special equations are derived to describe the effect of pin thread parameters on the material flow velocity inside thread grooves. These equations are combined with a three-dimensional transient CFD model to quantitatively analyze the effect of threaded pin profile on heat transfer and material flow in FSW. The results show that the average flow velocity and the downward z -component of material flow velocity near the pin side surface for threaded pin is higher than that for unthreaded pin. For a threaded pin, heat generation near pin side is a little bit increased, the area of TMAZ (thermo-mechanically affected zone) is broadened, especially the width of TMAZ near the bottom surface of the workpiece, and the pin thread can effectively improve the material flow near the pin tip. The calculated and measured thermal cycles and TMAZ boundary match with each other. Compared with the sliding mesh method, this model is easier to ensure the numerical robustness and save computational time.